Acute phase of aortic dissection: a pilot study on CD40L, MPO, and MMP-1, -2, 9 and TIMP-1 circulating levels in elderly patients. Issue 1 (December 2016) - Vianello, E.; Dozio, E.; Rigolini, R.; Marrocco-Trischitta, M.; Tacchini, L.; Trimarchi, S.; Corsi Romanelli, M.
Abstract Background Acute aortic dissection (AAD) is an event which may be rapidly fatal without early diagnosis and treatment. Aging is one of the main risk factors that could leading to AAD. To date, no specific biomarkers are available to increase the speed of diagnosis. CD40 ligand (CD40L), myeloperoxidase (MPO), matrix metalloproteinase (MMP)-1, -2, -9 and metallopeptidase tissue inhibitor 1 (TIMP-1) are biologically related molecules which integrate inflammation, tissue injury and remodeling, all events associated to AAD. Our is a pilot study to evaluate whether circulating levels of these molecules may be used as potential biomarkers in timely diagnosis of AAD. Results Within 24 h of symptom onset, circulating CD40L, MPO, MMP-1, -2, -9 and TIMP-1 were quantified by enzyme-linked immunosorbent assays in 22 patients (40–86 years of age) with AAD of ascending aorta (type A according to Stanford classification) and 11 patients with AAD of descending aorta (type B). 30 healthy individuals age matched were used as control group compared to controls, both type A and B AAD patients had higher CD40L (p  < 0.001) and MPO (p  < 0.01) levels. MMP-1 was higher in the overall AAD group (p  < 0.01). After Stanford classification, type A group had increased level compared to both control and type B (p  < 0.01 andp  < 0.05, respectively). TIMP-1 was higher in both A and B groups compared to controls (p  < 0.001). No differences were observed in MMP-2 and MMP-9 levels. Conclusions The simultaneous evaluation of CD40L, MPO and MMP-1 and TIMP-1, which may contribute to structural changes in aortic tissue in AAD patients, seems to be a novel promising diagnostic panel.